Transcriptional Remodeling in Primary Hippocampal Astrocytes from an Alzheimer's Disease Mouse Model - Ruffinatti, F.; Tapella, L.; Gregnanin, I.; Stevano, A.; Chiorino, G.; Canonico, P.L.; Distasi, C.; Genazzani, A.A.; Lim, D. (Current Alzheimer Research, 2018)
Background: It is well known that alterations in astrocytes occur in Alzheimer's disease and reactive astrogliosis is one of the hallmarks of the disease. Recently, data has emerged that suggests that alterations in astrocytes may also occur early in the pathogenesis of the disease. Objective: The aim of present work was to characterize the transcriptional alterations occurring in cultured astrocytes from 3xTg-AD mouse pups compared to control non-transgenic mice. Furthermore, we also compared these changes to those reported by others in astrocytes from symptomatic AD mice. Method: We conducted a whole-genome microarray study on primary cultured astrocytes from the hippocampus of 3xTg-AD and non-transgenic mouse newborn pups. We used cross-platform normalization and an unsupervised hierarchical clustering algorithm to compare our results with other datasets of cultured or freshly isolated astrocytes, including those isolated from plaque-stage APPswe/PS1dE9 AD mice. Results: We found a set of 993 genes differentially expressed in 3xTg-AD as compared with non-Tg astrocytes. Over-represented gene ontology terms were related to calcium, cell-cell communication, mitochondria, transcription, nucleotide binding and phosphorylation. Of note, no genes related to inflammation were found in cultured 3xTg-AD astrocytes. Comparison with astrocytes isolated from plaque stage APPswe/PS1dE9 showed that 882 out of 993 genes were selectively changed in primary 3xTg-AD astrocytes while 50 genes were co-regulated and 61 were anti-regulated (regulated in the opposite direction in the datasets). Conclusion: Our data show that in cultured astrocytes from an AD mouse model, transcriptional changes occur and are different from those reported in models mimicking later stages of the disease.
Keywords: FAD mutations